Biocontamination in the dairy industry: The effect of raw milk conditioning film on the adhesion of Escherichia coli - Zakariyae El hafa; Ikhlas Hani Chennoufi; Hafida Zahir; Mostafa El louali; Hassan Latrache (Czech Journal of Food Sciences)
Conditioning films on surfaces employed in the dairy industry serve as the precursors to the formation of pathogenic biofilms that impact product quality and consumer safety. Conditioning films have been studied from several aspects. However, there has been no study that evaluated the effect of raw milk conditioning film on the adhesion of Escherichia coli. This study investigated the adhesion of E. coli on glass and stainless-steel surfaces conditioned with raw milk and explored the surface properties potentially influencing this adhesion using the contact angle method. The results showed that after treating surfaces with raw milk, the adhesion of the bacteria on stainless steel and glass was significantly altered. Adhesion increased significantly on stainless steel (from 0.55 log10 to 2.8 log10) but it decreased on glass (from 1.56 log10 to 0.8 log10). Significant alterations were observed in the physicochemical properties of the surfaces. Glass was initially relatively hydrophilic (46.33°), while stainless steel was relatively hydrophobic (82.5°). After treatment, the glass became relatively more hydrophobic (74.6°), and stainless steel became relatively more hydrophilic (69.4°). The electron donor/acceptor components of glass decreased after the treatment, while these components increased for stainless steel. The significant changes in adhesion were hypothesized to be due to the modification of surface properties by the raw milk.